Pengaruh Model Pembelajaran Means Ends Analysis (MEA) Terhadap Hasil Belajar Ips - Astutik, Fifin Anis (Prosiding University Research Colloquium, 2021)
This study to determine the effect to the Means Ends Analysis (MEA) learning model onsocial studies learning outocomes for IV grade students of Mamba’ul Hisan ElementarySchool, Magelang.This study uses a pre-experimental design research (nondesigns), whita one-grup pretst-posstest research design. Research subjects were selected by saturatedsampling. Samples were teken as many as 15 students. The metodh of data collection isdone by test. Validity test using product moment assistes by SPSS Statistic for windows25.0, reliability test using Cronbach’s alpha formula, difficulty index and discriminatingpower test using SPSS Statistic for windows 25.0. The analysis prerequisite test consistsof normality test using the help of SPSS Statistic for windows 24.0. Data analysis usednon-parametrik statistical techniques, namely the Wilcoxon Test/ Z Test assisted by IBMStatistic for windows SPSS 24.0 program.The results showed that the Means EndsAnalysis learning model had a positive effect on social studies learning outocomes. This isdeevidenced from the results of the Wilcoxon test analysis with Z count -3.449 with a sigvalue (2-tiled) 0.0001 < 0,05. Based on the result of the analysis and discussion, there aredifferences in the average score of the pretest results of 52,93 and the average posttestresults of 76,20. The results of this study can be concluded that the use of the Means EndsAnalysis (MEA) model has a positive effect on social studies learning outocomes.